High-performance SERS substrate based on perovskite quantum dot–graphene/nano-Au composites for ultrasensitive detection of rhodamine 6G and p-nitrophenol. Issue 28 (30th June 2021) - Wang, Jiangcai; Qiu, Cuicui; Pang, Hua; Wu, Junyu; Sun, Mengtao; Liu, Dameng
Abstract : The designed PQD–G/Au nanocomposite shows high performance for ultrasensitive detection of R6G and PNP, attributed to the synergistic effect of the EM enhancement of Au nanostructures and CM enhancement of PQD–G heterostructures. Abstract : The ultrasensitive surface-enhanced Raman spectroscopy (SERS) detection of trace organic pollutants is an important issue in environmental protection. However, the SERS detection performance easily suffers from poor sensitivity and reproducibility due to the limitations of materials. A high-performance substrate is necessary to control the plasmonic hotspots in a wide spectral range. In this work, a perovskite quantum dot–graphene/nano-Au (PQD–G/Au) composite was designed using the combination of ligand-assisted reprecipitation and spinning coating techniques. The SERS performance of PQD–G/Au composites showed a strong dependence on their synthesis parameters, which was proved by the finite-difference time-domain program simulation. An excellent SERS detection behavior was obtained on the PQD–G/Au composite for rhodamine 6G (R6G) and p -nitrophenol (PNP) with a large linear detection range (10 −12 to 10 −6 M for R6G and 10 −8 to 10 −4 M for PNP) and a low detection limit (6.02 × 10 −13 M for R6G and 2.95 × 10 −9 M for PNP). The superior SERS performance was attributed to the synergistic effect of the electromagnetic enhancement of Au nanostructures and chemical enhancement of PQD–G heterostructures. The proposed method paves a new practical application of other 2D materials and heterostructures for designing a novel PQD-based SERS substrate.